Thermal Destabilization of Rhizomucor miehei Rennet with Aldehyde Dextran Sulfate: Purification, Bioconjugation and Milk-Clotting Activities - Celebi, Mithat; Topuzogullari, Murat; Kuzu, Huriye (HUMANA PRESS INC, 2016)
High thermal stability of Rhizomucor miehei Rennet, which is a thermostable enzyme used in cheese production, causes undesired cases at elevated temperatures. This study aims to decrease the thermal stability of the R. miehei Rennet at high temperatures. To achieve this goal, bioconjugates of R. miehei Rennet with aldehyde derivative of dextran sulfate were synthesized in different molar ratios. Physico-chemical properties of bioconjugates were characterized with particle size analyzer and gel permeation chromatography (GPC) techniques. The enzyme and biopolymer were conjugated with medium efficiency. Milk-clotting activities of bioconjugates decreased drastically at high temperatures in all molar ratios, which reveals that covalent bioconjugation of the enzyme with aldehyde derivative of dextran sulfate caused a decrease in thermal resistance of this enzyme.
Keywords: Bioconjugation; Dextran sulfate; Milk-clotting activity; Rhizomucor miehei Rennet; Purification; Thermal destabilization; MUCOR-MIEHEI; SKIM MILK; HORSERADISH-PEROXIDASE; COAGULATION; STABILIZATION; BIOPOLYMER; PROTEINS; PROTEASE; ENZYMES; Biochemistry & Molecular Biology; Biotechnology & Applied Microbiology